Subitizing reflects visuo-spatial object individuation capacity - Piazza, Manuela; Fumarola, Antonia; Chinello, Alessandro; Melcher, David (Cognition, 2011)
► Subitizing may reflect a capacity limited mechanism for multiple object individuation. ► We compare capacity in enumeration and in visuo-spatial short term memory tasks. ► Capacity in the two tasks correlate across subjects and is reduced in dual task conditions. ► Results are predicted assuming a common mechanism for individuation. Subitizing is the immediate apprehension of the exact number of items in small sets. Despite more than a 100 years of research around this phenomenon, its nature and origin are still unknown. One view posits that it reflects a number estimation process common for small and large sets, which precision decreases as the number of items increases, according to Weber’s law. Another view proposes that it reflects a non-numerical mechanism of visual indexing of multiple objects in parallel that is limited in capacity. In a previous research we have gathered evidence against the Weberian estimation hypothesis. Here we provide first direct evidence for the alternative object indexing hypothesis, and show that subitizing reflects a domain general mechanism shared with other tasks that require multiple object individuation.